Performance Audit of Indian System of Medicines and Homeopathy in West Bengal (1999-2004) - CAG of India (CAG of India, 2005)
The policy of the Government of India was to develop Indian System of Medicine and Homoeopathy (ISM&H) to provide better and economic health care to every citizen. This performance review of ISM&H in West Bengal covering the period 1999-2004 revealed that proper treatment through ISM&H could not be provided to the population due to low budgetary provision and failure of the institutions to avail of GOI assistance for infrastructure development, inadequate infrastructural facilities in state hospitals, non-deployment of medical officers in dispensaries and absence of homoeo dispensaries at panchayat level. In the absence of monitoring and supervision, the performance of the ISM&H institutions, laboratory and pharmacy and the utilisation of existing infrastructures for education, treatment and production of medicines were not satisfactory. Only 20 per cent of the gram panchayats were provided with dispensaries. State homoeopathic hospitals were set up only in Kolkata and two districts out of 19 districts. Fifty one dispensaries remained non-functional upto seven years for want of MOs. In the absence of essential indoor departments and requisite instruments in ISM&H institutions, patients were deprived of medical care and the students did not receive appropriate training. The existing capacity of the Integrated Drug Production and Testing Centre at Kalyani in drug testing and production of medicines and raw materials was badly underutilised. Modernisation of the Centre was stalled for want of infrastructure. Absence of supervision and monitoring on the part of the administration on utilisation of available infrastructure for education, treatment, production of medicine and supply of quality drugs adversely affected the quality of services under ISM&H.
For the Period 1999-2000 to 2003-04